Performance of Education Personnel in Administration in the Implementation of Office Administration - Sirajuddin Saleh; St. Rahayu Ningsih; Jamaluddin Jamaluddin (Pinisi Journal of Education and Management, 2023)
Employee performance is a result of work achieved by employees in carrying out their duties in accordance with the responsibilities given, therefore the purpose of this study is to be achieved to determine the performance of administrative education personnel in the implementation of office administration at SMA Negeri 5 Jeneponto. This research is a qualitative descriptive research. The data collection techniques used are observation methods, interview methods and documentation methods. The data analysis techniques used by this study are data analysis models Miles, Huberman and Saldana, namely data collection, data condensation, data presentation and conclusions. The number of informants in this study was 5 people, namely 1 principal and 4 administrative education staff. The results of this study show that the performance of administrative education personnel in the implementation of office administration at SMA Negeri 5 Jeneponto is quite good for the performance of office administration implementation, this is indicated by the results of research on each indicator, namely: quality of work, quantity of work, punctuality and effectiveness. This research is used as a source of information and knowledge about the performance of administrative employees on the implementation of office administration in more depth.